Oxidation of amylose and amylopectin by hydroxyl radicals assessed by electrospray ionisation mass spectrometry. (5th September 2016) - Simões, Joana; Moreira, Ana S.P.; da Costa, Elisabete; Evtyugin, Dmitry; Domingues, Pedro; Nunes, Fernando M.; Coimbra, Manuel A.; Domingues, M. Rosário M.
Graphical abstract: Highlights: Oxidation of amylose, amylopectin and maltotriose was induced by HO. The oxidised products were structurally characterized by mass spectrometry. A series of neutral and acidic oxidation derivatives were identified. The oxidation products formed from amylose and amylopectin were similar. Oxidation of internal and terminal reducing units in the polysaccharide was assessed. Abstract: The hydroxyl radicals (HO) are one of the most reactive oxygen species (ROS) involved in the oxidative damage of biological molecules, including carbohydrates. During the industrial processing of food, ROS can be formed. In order to identify the structural changes induced in starch by oxidation, amylose, amylopectin, and maltotriose, an oligosaccharide structurally related to these polysaccharides, were subjected to oxidation with HO generated under Fenton reaction conditions (Fe 2+ /H2 O2 ). The oxidised polysaccharides were hydrolysed by α-amylase and the obtained oligosaccharides were fractionated by ligand-exchange/size-exclusion chromatography. Both acidic and neutral α-amylase resistant oligosaccharides were characterized by mass spectrometry. In oxidised neutral products, new keto, hydroxyl, and hydroperoxy moieties, and oxidative ring scission were observed at the reducing end of the oligosaccharides. The acid sugar residues occurred at the reducing end and included gluconic and glucuronic acid derivatives, and acids formed by oxidative ring scission, namely, arabinonic, erythronic, glyceric and glycolic acids.